2019
DOI: 10.29328/journal.jccm.1001075
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the effect of coronary artery bypass grafting on the right ventricular function using speckle tracking echocardiography

Abstract: Purpose: This was a prospective study conducted at Benha University hospital and National Heart Institute on one hundred patients undwent coronary artery bypass grafting (CABG) to evaluate the effect of CABG on the right ventricular (RV) function using speckle tracking echocardiography (STE). Methods: All cases were subjected to detailed medical history, full physical examination, 12 leads electrocardiogram (ECG), routine laboratory tests including (complete blood picture, liver functions, renal functions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Recently, others have investigated the observation of normal global RV output and altered regional RV contractile patterns after CS with advanced speckle tracking by directly measuring RV longitudinal and transverse displacement and peak systolic strain, a measure of myocardial fiber contractile movement [ 32 , 45 , 46 , 51 - 53 ]. Strain is a measure of myocardial deformation, a change in the length of a segment relative to its baseline length.…”
Section: Right Ventricular Function and Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, others have investigated the observation of normal global RV output and altered regional RV contractile patterns after CS with advanced speckle tracking by directly measuring RV longitudinal and transverse displacement and peak systolic strain, a measure of myocardial fiber contractile movement [ 32 , 45 , 46 , 51 - 53 ]. Strain is a measure of myocardial deformation, a change in the length of a segment relative to its baseline length.…”
Section: Right Ventricular Function and Cardiac Surgerymentioning
confidence: 99%
“…Some studies have shown no reduction in septal strain in CABG patients [ 46 , 53 , 55 ]. Others have reported a decrease in septal strain [ 51 , 52 ]. Donauer studied RV and septal strain in 30 patients undergoing CABG [ 52 ].…”
Section: Right Ventricular Function and Surgical Approachmentioning
confidence: 99%